Role of Artificial Intelligence in Prevention and Detection of Covid-19 - Javed Shaikh, P.Suganda Devi, Mohammad Arif Shaikh, K.A.Nafee, Tadesse Hailu (International Journal of Advanced Science and Technology, 2020)
Currently the whole world is facing major challenges in tackling COVID-19. From Dec 2019 to till date COVID -19 has affected majority countries of the world. Many organizations and scientists are working on finding a vaccine and the way in which the spread of the COVID-19 can be minimized. One technology which can be effective in tackling with this virus is Artificial Intelligence (AI). Artificial intelligence has worked very well in case of other diseases and it has the potential to help us deal with COVID-19 virus too. It is the information and creativity of the people who use it that can help in findings solution to this issue. AI has played important role in virus prevention and detection in several previous instances. Due to COVID-19 crisis we have a chance to uncover some of the features of AI. Machine learning which a subclass of AI is is used to recognize patterns in recorded data sets and prepare useful information based on it. At the point where utilized to its full extent, AI can possibly surpass human efforts through speed as well as by distinguishing designs in information that were earlier disregarded. However, for successful implementation of AI systems lot of accurate and relevant data is needed. This paper attempts to describe the role of AI in prevention and detection of COVID-19 and deals with different technical aspects of AI. This paper also explains the domains where AI can help to stop spread of COVID-19 with probable solutions.